PENINGKATAN PENGETAHUAN REMAJA DALAM UPAYA PENCEGAHAN STUNTING MELALUI SOSIALISASI PENCEGAHAN PERNIKAHAN DINI DI DESA TERATAK, BATUKLIANG UTARA - Putri, Fitria Agustina Budiono; Permadi, Dena Indiarto; Aninfento, Deanaldo Setiawan; Muhidayani, Respi Eka Septi; Surachman, Dyah Fortuna; Ijah, Uswatun; Mustaqrobin, Achmad Sajidan; Muslihatun, Muslihatun; Hadi, Irfan Zikrul; Hannisa, Pina; Hayati, Hayati (Universitas Mataram, 2024)
Child marriage is a marriage carried out under the age of 19 years. The early marriage prevention socialization program implemented by the Mataram University Real Work Lecture (KKN) at SMPN 1 Batukliang Utara and SMAN 1 Batukliang Utara, Central Lombok Regency takes the form of counseling on the prevention of early marriage for teenagers. - Adolescents who are still underage are one way to reduce the number of cases of early marriage. With this, the aim of the KKN program can be successful and in line with the target of increasing cases of early marriage in Indonesia in 2018. Based on the results of the questionnaire given before and after the delivery of the material, it was seen that the average increase in students' knowledge from the pretest from 2.4000 and the posttest from 3.3400 to 0.9400. This is a good sign because the education provided is proven to be acceptable and it is hoped that participants can implement this knowledge. Students' knowledge of this is one of the most important factors in efforts to prevent early marriage.